Optimization of lipase catalysed synthesis of xylose caproate ester in organic solvent - Hamidon, Noor Fazrieyana (2016)
Lipase catalysed synthesis of xylose caproate ester was performed by condensation of xylose, an aldopentose, and caproic acid in organic solvents. A dual-solvent system containing dimethylsulfoxide (DMSO) and acetone (1:10, v/v) was used to determine the optimal conditions for the reaction. Different reaction parameters (solvent system, reaction time, substrate molar ratio and the amount of enzyme loaded) were studied. The highest conversion rate (64%) was obtained within 24 hours with the optimal conditions of 16% (w/v) Novozym 435 and a molar ratio of xylose to caproic acid of 1:4 (mmol). Xylose caproate ester was purified and characterized by thin layer chromatography (TLC), high performance liquid chromatography (HPLC), fourier transform infrared spectroscopy (FTIR), gas chromatography flame ionization (GCFID), gas chromatography mass spectrometry (GCMS) and nuclear magnetic resonance (NMR). The pure product existed as a waxy solid form with bright yellow color. The melting point, hydrophilic lipophipic value (HLB), and solubility of the product was evaluated.